Rejuvenating the flowing sanctity of Panatirtha : enhancing the natural and cultural tourism of Panatirtha, Tahirpur through architectural and planning intervention - Nitu, Upama Das (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2023.